Factors related to the behavior of seeking health services in community experiencing symptoms of covid-19 - Tonasih Tonasih; Nunung Nurjanah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Coronavirus is a group of viruses that can cause disease in animals or humans. Positive confirmed cases of Covid-19 in Cirebon Regency, West Java, during 1-28 August 2020 reached 193 people while the number of deaths due to Covid-19 in Cirebon City, West Java, again increased by 17 people died. The causes of Covid-19 death include patients receiving late treatment due to the less than optimal level of occupancy in the treatment area and monitoring of COVID-19 patients who are self-isolating. In addition, it is also caused by isoman patients with severe symptoms, patient overload, scarcity of drugs and oxygen, the health system is not ready, the health sub-system of community empowerment has failed. there are still many people who still consider being exposed to the corona virus as a disgrace, so they don't want to go to health facilities. People who are sick in many areas, are still seen as tainted, condemned, unkind people. does not want to be tested, does not want to report, because he has a social burden.Purpose: This study aims to determine the factors related to the behavior of seeking health services in the community if experiencing symptoms of Covid-19 in Cirebon.Methods: This study used a cross sectional design. This research was conducted at Arsy Medika Clinic, Cirebon Regency and Akbid Muhammadiyah Clinic, Cirebon City on 18-25 September 2021 and obtained a sample of 87 respondents.Results: The results showed that most of the respondents were 20-29 years old, the gender of the respondents was female, the respondent's education was high school, the respondent's occupation was not working, married, received information from television, there was a relationship between age and education with health service seeking behavior, and there was no relationship between age and education. there is a relationship between gender, occupation, marital status, information media, and knowledge with health service seeking behavior.Conclusion: This study shows that there is a relationship between age and education with health service seeking behavior, and there is no relationship between gender, occupation, marital status, information media, and knowledge with health service seeking behavior.